THE PREVALENCE OF CELIAC DISEASE IN PATIENTS WITH IRON-DEFICIENCY ANEMIA IN CENTER AND SOUTH AREA OF IRAN - Mahmud BAGHBANIAN; Ali FARAHAT; Hasan Ali VAHEDIAN; Elham SHEYDA; Mohamad Reza ZARE-KHORMIZI (Arquivos de Gastroenterologia, 2015)
Background - Celiac disease is an immune-mediated enteropathy due to a permanent sensitivity to gluten in genetically susceptible people. Iron-deficiency anemia is the most widely experienced anemia in humans. Iron-deficiency anemia additionally is a common extra intestinal manifestation of celiac disease. Objective - To investigate correlation between tTg levels and histological alterations and then to determine the prevalence of celiac disease in Center and South area patients of Iran with iron deficiency anemia. Methods - A total of 402 patients aged 12-78 years who presented with iron-deficiency anemia were included in this study. Hemoglobin, mean corpuscular volume and serum ferritin were determined. Venous blood samples for anti-tissue transglutaminase antibody immunoglobuline A and G were obtained from these patients. Upper gastrointestinal endoscopy was recommended to patients who had positive serology. Results - Of 402 patients with iron-deficiency anemia, 42 (10.4%) had positive serology for celiac disease. The small intestine biopsy of all patients with positive serology showed pathological changes (Marsh I, II & III). There was not significant difference in the mean hemoglobin level between iron-deficiency anemia patients with celiac disease and without celiac disease, duodenal biopsy results did not show significant relationship between the severity of pathological changes and levels of anti-tTG IgG (P -value: 0/869) but significant relationship was discovered between pathological changes and levels of anti-tTG IgA (P -value: 0/004). Conclusion - Screening of celiac disease by anti-tissue transglutaminase antibody should be completed as a routine investigation in patients with iron-deficiency anemia. Also physicians must consider celiac disease as a possible reason of anemia in all patients with iron deficiency anemia.